Recent advances on the roles of LncRNAs in cardiovascular disease - Fang, Yexian; Xu, Yuerong; Wang, Runze; Hu, Lang; Guo, Dong; Xue, Feng; Guo, Wangang; Zhang, Dongwei; Hu, Jianqiang; Li, Yan; Zhang, Wei; Zhang, Mingming (Journal of cellular and molecular medicine, 2020)
Cardiovascular diseases are a main cause of mortality whose prevalence continues to increase worldwide. Long non‐coding RNAs (lncRNAs) regulate a variety of biological processes by modifying and regulating transcription of coding genes, directly binding to proteins and even coding proteins themselves. LncRNAs play key roles in the occurrence and development of myocardial infarction, heart failure, myocardial hypertrophy, arrhythmias and other pathological processes that significantly affect the prognosis and survival of patients with cardiovascular diseases. We here review the latest research on lncRNAs in cardiovascular diseases as a basis to formulate future research on prevention and treatment of cardiovascular diseases.